Improving Chemistry Learning Outcomes with Jigsaw for Biology Education Students - Apsari , Mirza Roma (IJCER (International Journal of Chemistry Education Research), 2025)
This study aims to overcome the difficulties experienced by biology education students in studying basic chemistry courses, with a primary focus on improving their learning outcomes. Before conducting the research, a survey questionnaire on learning difficulties in chemistry was conducted. Based on the results of the questionnaire survey, many students which 58.3% of students reported having significant difficulty in studying chemistry, while 41.7% agreed that chemistry was difficult. consider chemistry a difficult subject, resulting in a lack of motivation, boredom, drowsiness, and difficulty understanding the material in a short time. To address this challenge, the jigsaw cooperative learning model is applied. In this approach, students are divided into two groups: the original group and the expert group. The expert group is tasked with exploring and discussing certain topics, which are then shared with the original group. Before learning begins, students are given a pretest to measure their initial understanding, followed by the learning process using the jigsaw model, and ending with a posttest to assess the increase in understanding. The increase in learning outcomes is calculated using the N-Gain score, and the analysis results show that the average N-Gain score across the four basic chemistry subtopics (the nature of chemistry, scientific methods, the classification of materials in chemistry, and the physical and chemical properties of materials) falls into the high improvement category. These findings indicate that the application of the jigsaw cooperative model is effective in improving chemistry learning outcomes for students majoring in biology education. Additionally, the results of the learning satisfaction questionnaire indicate that the learning process runs smoothly and without significant obstacles, allowing for optimal learning outcomes.